A matter of time… consideration of future consequences and temporal distance contribute to the ideology gap in climate change scepticism. (December 2021) - Većkalov, Bojana; Zarzeczna, Natalia; Niehoff, Esther; McPhetres, Jonathon; Rutjens, Bastiaan T.
Abstract: Factors that contribute to the well-established ideology gap in climate change beliefs (i.e., conservatives' scepticism about climate change and its severity) remain underexplored. In the present research, we propose that there are differences in the consideration of future consequences, as well as the perception of climate change in time, between conservatives and liberals which, in part, contribute to this gap. Across three studies (total N  = 654) in the Netherlands and the UK, we demonstrate that, compared to liberals, conservatives tend to consider future consequences of their behaviour less and perceive the effects of climate change as further away in the future. Furthermore, we find that temporal distance to climate change, and, to a lesser extent, consideration of future consequences, can partially account for higher levels of scepticism about climate change on the conservative side of the ideological spectrum. Besides contributing to a better understanding of this ideology bias, these results have implications for climate change communication. Highlights: Political conservatives are more sceptical about climate change than liberals. Psychological contributors to this gap in climate change beliefs are understudied. Conservatives consider the future consequences of their behaviour less than liberals. Conservatives also perceive climate change consequences as further away in time. These two tendencies can partly account for the ideological gap in climate beliefs.